2020
DOI: 10.1097/md.0000000000022568
|View full text |Cite
|
Sign up to set email alerts
|

Impact of intraoperative allogenic and autologous transfusion on immune function and prognosis in patients with hepatocellular carcinoma

Abstract: The effect of intraoperative blood transfusion on the immune function and prognosis of hepatocellular carcinoma (HCC) has not been fully investigated. The aim of this study was to evaluate the effects of intraoperative autologous blood transfusion and allogeneic blood transfusion on immune function and prognosis in surgically treated HCC patients. One hundred fourteen primary hepatic carcinoma patients who would undergo selective operations were divided into two groups, 35 patients in the experimental group re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…There is ongoing debate about the long-term effects of autologous blood transfusion on cancer patients after surgery. Gong Y et al [24] analyzed 114 patients with liver cancer who received perioperative infusion of autologous blood and allogeneic blood and concluded that reinfusion of stored autologous blood can shorten the time of postoperative immunosuppression by reducing the infusion of allogeneic blood, thereby improving the recurrence rate of postoperative liver cancer and prolonging the survival time of patients. This team also examined postoperative lymphocytes (CD3+, CD4+, CD4+/CD8 + T cells, NK cells) and immune-related proteins (IgG, IgA, IgM) in patients with liver cancer and found that lymphocytes and immune-related proteins returned to normal in the autologous blood transfusion group on the fth day but that they were signi cantly lower in the allogeneic blood transfusion group, indicating that allogeneic blood transfusion can inhibit the immune system but that autologous blood transfusion has little effect on the immune system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is ongoing debate about the long-term effects of autologous blood transfusion on cancer patients after surgery. Gong Y et al [24] analyzed 114 patients with liver cancer who received perioperative infusion of autologous blood and allogeneic blood and concluded that reinfusion of stored autologous blood can shorten the time of postoperative immunosuppression by reducing the infusion of allogeneic blood, thereby improving the recurrence rate of postoperative liver cancer and prolonging the survival time of patients. This team also examined postoperative lymphocytes (CD3+, CD4+, CD4+/CD8 + T cells, NK cells) and immune-related proteins (IgG, IgA, IgM) in patients with liver cancer and found that lymphocytes and immune-related proteins returned to normal in the autologous blood transfusion group on the fth day but that they were signi cantly lower in the allogeneic blood transfusion group, indicating that allogeneic blood transfusion can inhibit the immune system but that autologous blood transfusion has little effect on the immune system.…”
Section: Discussionmentioning
confidence: 99%
“…Common autologous blood transfusion types include intraoperative salvage autotransfusion (ISA), predeposit autologous transfusion (PAT) and acute normovolemic hemodilution (ANH). Because they effectively reduce the amount of allogeneic blood transfusion, it has been reported that ISA and PAT can minimize the negative impact of blood transfusion on postoperative tumor recurrence [24,25]. However, there are few studies on the correlation between ANH and postoperative recurrence of tumors, and it is still unclear whether acute isovolumic dilution autologous blood transfusion has a positive or negative in uence on the long-term outcome of tumors.…”
Section: Introductionmentioning
confidence: 99%
“…A reduction in the activities of natural killer cells and helper T cells as well as an increase in suppressor T-cell activity and decrease in the absolute peripheral blood lymphocyte count were observed in patients who received blood transfusions [23,24]. Autologous rather than allogenic blood transfusion is recommended in HCC patients because of the minimal effect on cellular immunity and possible improvement of immunosuppression during the postoperative period [25]. In contrast, recent studies have found no association of blood transfusion with post-resection disease-free and overall survival rates in HCC [22,26].…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study showed that CD3+, CD4+ levels and CD4+/CD8+ ratios were lower in the 2 groups of puerperae on the first postoperative day compared to those before the surgery, suggesting a decrease in the puerperae' cellular immune function; The reason for this may be related to the absence of immunoneutral effectors in autologous blood. [26,32,33] There are limitations to this study. The small sample size of the subjects included in this study resulted in the benefits of autotransfusion possibly not being fully realized.…”
Section: Groupmentioning
confidence: 96%